Telehealth use in emergency care during coronavirus disease 2019: a systematic review. Issue 3 (1st May 2021) - Jaffe, Todd A.; Hayden, Emily; Uscher‐Pines, Lori; Sousa, Jessica; Schwamm, Lee H.; Mehrotra, Ateev; Zachrison, Kori S.
Abstract: Objective: The coronavirus disease 2019 pandemic has presented emergency departments (EDs) with many challenges to address the acute care needs of patients. Many EDs have leveraged telehealth to innovatively respond to these challenges. This review describes the landscape of telehealth initiatives in emergency care that have been described during the coronavirus disease 2019 pandemic. Methods: We conducted a comprehensive, systematic review of the literature using PubMed, supplemented by a review of the gray literature (ie, non‐peer reviewed), with input from subject matter experts to identify telehealth initiatives in emergency care during coronavirus disease 2019. We categorized types of telehealth use based on purpose and user characteristics. Results: We included 27 papers from our review of the medical literature and another 8 sources from gray literature review. The vast majority of studies (32/35) were descriptive in nature, with the additional inclusion of 2 cohort studies and one randomized clinical trial. There were 5 categories of ED telehealth use during the pandemic: (1) pre‐ED evaluation and screening, (2) within ED (including as a means of limiting staff and patient exposure and facilitating consultation with specialists), (3) post‐ED discharge monitoring and treatment, (4) educating trainees and health care workers, and (5) coordinating resources and patient care. Conclusion: Telehealth has been used in a variety of manners during the coronavirus disease 2019 pandemic, enabling innovation in emergency care delivery. The findings from this study can be used by institutions to consider how telehealth may address challenges in emergency care during the coronavirus disease 2019 pandemic and beyond. Because few studies included cost data and given the variability in institutional resources, how organizations implement telehealth programs will likely vary. Future work should further explore barriers and facilitators of innovation, and the impact on care delivery and patient outcomes.